Bacterial nanocellulose, a sustainable alternative, to implement cleaner production in the design of biosensors to detect heavy metals in surface waters - González, Exequiel Elías (2023)
While high productivity is positive for growth in developing countries, environmental balance and moderation in pollution levels must be taken into consideration. The dumping of highly harmful industrial waste into river beds, streams, groundwater tables and underground freshwater reservoirs is a clear disadvantage when thinking about sustainable processes. Putting the environment first, we wonder how many thousands of liters of vinase and toxic waste run through our watersheds to end up reusing some bagasse to extract vegetal origin cellulose. It is not about demonizing the product, but rather applying cleaner production technologies to obtain it in a sustainable and ecologically friendly way. The main objective of this review is to propose nanocellulose of bacterial origin as an inert support material for biosensors that detect heavy methals on surface waters. This alternative is sustainable, resistant to temperature and high humidity levels, optical transparency, porous nanostructure and possibilities for surface functionalization. This material has advantages over vegetable cellulose, not only functional, but also from the aforementioned environmental perspective. Heavy metals contamination on surface waters is a global problem. The development of reliable, lightweight and portable biosensors is a necessity for in situ detection of the degree of contamination, without the need for cumbersome and often complex sample taking. The performance of a biosensor depends on its ability to immobilize receptors, maintaining their natural activity, against targets in solution, as is the case of our interest. When we propose bacterial nanocellulose as a support it is due to its ability to form covalent bonds and trap by cross-linking. Although due to their high surface area per unit of volume, physical methods are also a possibility that provides versatility of processes that adapt to multiple biosensor formats. Each new discovery of the potential functionalization for bacterial nanocellulose allows us to think of new, more efficient, more environmentally friendly sensors for a multitude of applications. As the contamination of water with heavy metals increases alarmingly due to over-industrialization, it is time to ask ourselves about the cognitive dissonance of using cellulose obtained by traditional means and the aforementioned contamination that they carry to generate sensors to measure the degree of pollution that we generate when producing it.